2011
DOI: 10.4061/2011/914849
|View full text |Cite
|
Sign up to set email alerts
|

Peritoneal Dialysis in Diabetics: There Is Room for More

Abstract: End stage renal disease diabetic patients suffer from worse clinical outcomes under dialysis-independently of modality. Peritoneal dialysis offers them the advantages of home therapy while sparing their frail vascular capital and preserving residual renal function. Other benefits and potential risks deserve discussion. Predialysis intervention with early nephrology referral, patient education, and multidisciplinary support are recommended. Skilled and updated peritoneal dialysis protocols must be prescribed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 82 publications
1
25
0
5
Order By: Relevance
“…A series of more than 400 patients showed that survival rate of diabetics on PD was equal to that of non‐diabetics on HD, and diabetics on HD had the worst survival . It has been suggested that new PD solutions with low accumulation of glucose degradation products may reduce the risk of cardiovascular disease in diabetic patients, by preserving residual renal function, optimizing volume control, and possibly reducing local and systemic inflammation …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A series of more than 400 patients showed that survival rate of diabetics on PD was equal to that of non‐diabetics on HD, and diabetics on HD had the worst survival . It has been suggested that new PD solutions with low accumulation of glucose degradation products may reduce the risk of cardiovascular disease in diabetic patients, by preserving residual renal function, optimizing volume control, and possibly reducing local and systemic inflammation …”
Section: Discussionmentioning
confidence: 99%
“…20,21 Several potential risks of PD in diabetic patients have been described (fluid overload, dysregulation of metabolic response to glucose, hyperinsulinemia, obesity, dyslipidemia, and peritoneal infection), but important benefits have also been reported (homebased continuous therapy, more liberal diet, intraperitoneal insulin administration, better preservation of residual renal function and blood pressure control, preservation of vascular access, avoidance of myocardial stunning and circulatory stress, and no need for systemic anticoagulation). 22 A series of more than 400 patients showed that survival rate of diabetics on PD was equal to that of nondiabetics on HD, and diabetics on HD had the worst survival. 23 It has been suggested that new PD solutions with low accumulation of glucose degradation products may reduce the risk of cardiovascular disease in diabetic patients, by preserving residual renal function, optimizing volume control, and possibly reducing local and systemic inflammation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is likely due to the high prevalence of CVD and metabolic complications in this population. 19,20 In our study, diabetes was the most common cause of ESRD. Despite the high rate of detection of DM in patients living less than 5 years, it did not affect patient survival significantly.…”
Section: Discussionmentioning
confidence: 58%
“…Several studies indicated that in PD patients insulin resistance and glucose overload may represent important factors that significantly influence glycemic variability [7]. The glucose excursions are exacerbated and difficult to assess due to the influence of both the uremic status and PD per se [8].…”
Section: Background and Aimsmentioning
confidence: 99%